Rileggendo la Summa Theologica di san Tommaso d’Aquino : Il trattato De Deo a partire dalla teologia di Réginald Garrigou-Lagrange - Bracchi, Marco (Sapientia, 2018)
This article is intended to analyse the internal unity in the treatise de Deo thanks to the interpretation offered by Réginald Garrigou-Lagrange (1877-1964) re-examining the questions from 2 to 26 of Summa Theologica’s Prima Pars by Saint Thomas Aquinas. The eminentia Deitatis thesis represents the keystone of the theological process’s reviewing started by Aquinas, so it arises a reference to the integrity of God’s interpretation and of his intimate life for a precise analysis. To know better the Being that is God and his act, means to understand better man and his last aim: the visio beatifica. That is why the nomination of God is not a secondary issue in the Catholic theology: we are not children of a God who has not a Face and a Name. Garrigou-Lagrange’s perspective is a fundamental guide to read Aquinas in this direction. The article hopes for a «rebirth» of God’s discussion from a classical point of view and a new analysis of Summa Theologica.